Affective rating of audio and video clips using the EmojiGrid - Toet, Alexander (F1000Res, 2021)
Background: In this study we measured the affective appraisal of sounds and video clips using a newly developed graphical self-report tool: the EmojiGrid. The EmojiGrid is a square grid, labeled with emoji that express different degrees of valence and arousal. Users rate the valence and arousal of a given stimulus by simply clicking on the grid. Methods: In Experiment I, observers (N=150, 74 males, mean age=25.2±3.5) used the EmojiGrid to rate their affective appraisal of 77 validated sound clips from nine different semantic categories, covering a large area of the affective space. In Experiment II, observers (N=60, 32 males, mean age=24.5±3.3) used the EmojiGrid to rate their affective appraisal of 50 validated film fragments varying in positive and negative affect (20 positive, 20 negative, 10 neutral). Results: The results of this study show that for both sound and video, the agreement between the mean ratings obtained with the EmojiGrid and those obtained with an alternative and validated affective rating tool in previous studies in the literature, is excellent for valence and good for arousal. Our results also show the typical universal U-shaped relation between mean valence and arousal that is commonly observed for affective sensory stimuli, both for sound and video. Conclusions: We conclude that the EmojiGrid can be used as an affective self-report tool for the assessment of sound and video-evoked emotions.